The Mind of Everyday Combining Individual and Artificial Intelligence - Papajorgji, Petraq; Moskowitz, Howard (Springer Nature Switzerland : Imprint: Springer, 2025)
XVIII, 260 p. 40 illus., 31 illus. in color.